Predictive role of circulating tumor DNA based molecular residual disease for long-term outcomes in non-small cell lung cancer patients: a meta-analysis - Siyuan Che; Dongliang Yu (World Journal of Surgical Oncology)
Abstract Purpose To identify the predictive role of circulating tumor DNA (ctDNA)-based molecular residual disease (MRD) for long-term outcomes in non-small cell lung cancer (NSCLC) patients. Methods Several databases were searched. The primary outcome was progression-free survival (PFS), and the secondary outcomes included overall survival (OS) and cancer-specific survival (CSS). Hazard ratios (HRs) and 95% confidence intervals (CIs) were combined, and subgroup analyses based on the time point of MRD detection (landmark vs. longitudinal) and treatment (surgery vs. chemoradiotherapy) were further performed. Results Ten studies with 1859 cases were included. Pooled results demonstrated that positive ctDNA MRD significantly predicted worse PFS (HR = 11.19, 95% CI: 6.10–20.52, P < 0.001), OS (HR = 6.34, 95% CI: 2.27–17.74, P < 0.001) and CSS (HR = 16.67, 95% CI: 10.00–25.00, P < 0.001). Subgroup analysis by the time points of MRD detection (landmark: HR = 8.93, P < 0.001; longitudinal: HR = 17.52, P < 0.001) and treatment (surgery: HR = 11.63, P < 0.001; chemoradiotherapy: HR = 5.56, P < 0.001) revealed consistent results. Conclusion ctDNA-based MRD could serve as a valuable prognostic indicator in NSCLC, and patients with positive ctDNA-based MRD are at significantly greater risk of recurrence and lower survival.